A new calcareous Globothalamea (Rhizaria, Foraminifera) from the northeastern Brazilian continental margin - Disaró, Sibelle Trevisan (2023)
Studying living benthic foraminifers from the northeastern Braziliancontinental margin for several years, we have recorded around 1,100 specieswith a tremendous foraminiferal richness. Many researchers were active in thelast century on the Tropical Southwest Atlantic. The possibility of beinginvolved in this research brings us a new understanding of the regionalforaminiferal biodiversity and promotes the discovery of a new speciespresenting now. Searching publications for similar species we had no success.Another difficulty was placing this new form in an adequate genus due tocertaindistinctive features; therefore, we probably have a new genus, too; fornow, we will call it Discorbinella (?) sp. nov.The test wasfrequently attached to bioclasts or lithoclasts but also free; it presents alow trochospiral arrangement, subcircular to oval outline, slightly lobed witha rounded periphery. It has a calcareous wall semi-transparent with milky whitecolor. The dorsal side is convex with 2.5 to 3 whorls, partially evolute. The suturesare gently curved and slightly depressed with a peculiar chamber overlappingdue to how the proximal portion of the subsequent chambers lays over the distalportion of the anterior one. It has 6 to 8 falciform to subrectangular chambersper whorl, increasing in size as added. Another notable characteristic is thelarge pores distributed over most of the spiral side, not uniform in size butalmost uniformly distributed, following the sutural direction on the dorsalside, giving a coarse appearance to the test. The umbilical side is involuteand slightly concave; sutures are sinuous, visible but obscured by theextensive development of papillae almost even in size, though they cover mostof the umbilical face except for the periphery, which shows a smooth stripewith pores, little ones. Umbilicus is covered by papillae from the chambers ofthe previous coil. The aperture is a small, simple opening on the periphery atthe base of the last chamber, another one on the umbilical side, under the wideflap projected towards the umbilicus. The height (mean ± SD) is 50.46 μm ±16.36, and the diameter is 166.20 μm ± 47.40. They live between 4 and 49 metersdeep. Considering the narrow continental shelf, they are found from the innerto the outer shelf on variable sediments: lithobioclastics, lithoclastics,biolithoclastics, and bioclastics.